Luxury fashion and culture - Woodside, Arch G.; Ko, Eunju (Emerald, 2013)
Luxury Fashion and Culture focuses on the study of how humans use high quality, highly pleasurable, and frequently rare products, services, and experiences to distinguish to themselves and others who they are as well as well as whom they are not both within and across cultures. Luxury fashion enables the individual to transform herselfto play a part in scenes exuding refinement, acceptance, high status, and good taste and risk ridicule by playing the part badly. The chapters provide new theory, recipes of methods, and findings on how culture helps humans manage and respond to luxury fashion enactments. Rather than focusing on traditional cultural transformations, it focuses on personal expressions of self and archetypal role-playing and fulfilment through the power of luxury fashion. This volume: applies the perspectives of Veblen, Goffman, McCracken, Thompson, and Belk to provide a theoretical foundation to explain why and how humans buy and enact luxury fashion products, services, and experiences. includes confirmatory personal introspections of explanations of luxury fashion enactments with self-photographs and self-interpretations of the enactments to explain how individuals enact luxury fashion and respond to alternative fashion-marketing designs. is unique in conjoining sociology, psychology, marketing, and economics to advance fashion marketing theory and research.
Includes index.
Keywords: Social Science -- Anthropology -- Cultural.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Fashion & society.; Consumerism.; Clothing and dress -- Social aspects.; Fashion -- Social aspects.; Women's clothing -- History.; Luxuries.; elektronické knihy; electronic books